Pembaruan Pendidikan Islam Perspektif Hamka - Shobahussurur Shobahussurur (TSAQAFAH, 2009)
Modernization in every aspect of life is definitely needed. Modernization is a process to construct soul to be independent. Modernization from feudalism to democracy. Modernization from the traditional agrarian to advance state and industrialized. Modernization from ignorance to scientific discoveries. Scientific modernization to challenge the advanced countries, and so on. Based on this fact, Hamka has a view that modernization of education is definitely needed. That is because of serious problem in the world of education in Indonesia. Furthermore, the Western education results a sense of antipathy toward Islam and at the same time, Islamic boarding school education mostly against the western world. According to Hamka modernization of education can be actualized through the role of mosque. Mosque has effective educational role and enlightenment, but at some mosques rise educational institutions, for the level of schools as well as university.